Penerapan Aplikasi Lamikro Sebagai Solusi Pemulihan UMKM Pasca Pandemi - I Gusti Agung Jaya Utama; Ni Made Trisya Narindi; Putu Ayu Wulan Laksintiyani (Jurnal Akuntansi, 2022)
The Covid-19 pandemic has had a major impact on the weakening economy in Indonesia. One of the sectors that will be affected is MSMEs. The existence of restrictions on mobility and the decline in people's purchasing power makes MSMEs experience a decrease in income. This is exacerbated by the difficulty of MSMEs in accessing capital and financing because many MSMEs are not yet bankable. So that through this research, an analysis related to the understanding and application of accounting by MSME actors is presented and the urgency of the application of accounting tools in the form of the LAMIKRO application as an effort to recover MSMEs after the pandemic. The measurement of understanding is reviewed through the relationship of three independent variables, namely accounting understanding, perceived usefulness, and internal factors. This study was conducted on 17 samples of MSMEs selected through non-random sampling on the MSME population in Sidemen village. The research method used is a qualitative method in which data collection is carried out through questionnaires and literature studies. The results showed that the understanding and application of accounting knowledge to MSMEs in Sidemen Village was not optimal, while the perception of usefulness and internal factors had a significant effect on the application of the LAMIKRO application, and the three variables together influenced the success of MSME recovery. The implementation of the LAMIKRO application as a tool for the financial reporting system launched by the government is considered to have high urgency to be applied by MSME actors in Indonesia. Keywords:  Understanding, Application, LAMIKRO Application Urgency, and Recovery of MSMEs After the Pandemic